Bamboo Gods and bionic boys a brief history of the Philippines’ B films - Leavold, Andrew (Plaridel, 2014)
Access online through this link: https://www.plarideljournal.org/article/bamboo-gods-and-bionic-boys-a-brief-history-of-the-philippines-b-films